How the South African headquarter company regime compares to other jurisdictions - Crowley, Michelle (My University, 2020)
Attraction of foreign direct investment has been identified as one of South Africa’s strategic economic focuses. In 2011 a headquarter tax regime was introduced with the aim of attracting multinationals to set up headquarters for investment into the rest of Africa through South Africa. The headquarter company regime has not been as successful as expected and was identified by the Davis Tax Committee as a regime that needs to be examined by National Treasury. This study examines and compares tax incentives, policy, anti-avoidance and practical considerations of what multinational companies consider attractive to the headquarter company regime and contrasts these with similar incentives offered by selected countries
A research report to be submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce specialising in Taxation, 2020